Shear-bond behavior of self-compacting geopolymer concrete to conventional concrete. (28th February 2022) - Purwanto,; Ekaputri, Januarti Jaya; Nuroji,; Indriyantho, Bobby Rio; Han, Aylie; Gan, Buntara Sthenly
Abstract: The shear-bond behavior of two mechanically different concretes is fundamental when conducting external reinforcement, retrofitting, or repair. The two components are designed to possess full strain compatibility in sustaining the stress transfer between the two parts throughout the loading sequence. This work investigated the shear-bond behavior between conventional and self-compacting geopolymer concrete based on the push-off method. The influence of surface roughness on the bond behavior was studied, and a finite element model was constructed and validated to the experimental data. Surprisingly, the chemical bond characteristics of geopolymer concrete have little effect on the bond strength as compared to conventional concrete having the same compression strengths, but significantly influences the load-slip pattern of the interface. As expected, the bond strength was positively influenced by the interface roughness. All failure modes were unmistakably brittle. The strain deformation pattern generated from the finite element model underlined that large strains and stresses were present at the far ends in the interface, where initial cracking was detected in these regions. The study concluded that self-compacting geopolymer concrete is a perfect solution for older structure's external strengthening or retrofitting. This material has a better sustainable and a more environmentally friendly character. Highlights: Shear-bond strength of conventional and geopolymer concrete was compared. Effect of a grooved surface was looked into. Load-slip and stiffness behavior also initial crack and propagation were observed. Finite element model was constructed using double nodes and springs at interfaces. Stress concentration underlined the stress distribution and initial cracking.